New frontiers in artificial intelligence : JSAI-isAI Workshops, JURISIN, SKL, AI-Biz, LENLS, AAA, SCIDOCA, kNeXI, Tsukuba, Tokyo, November 13-15, 2017, Revised selected papers /: JSAI-isAI Workshops, JURISIN, SKL, AI-Biz, LENLS, AAA, SCIDOCA, kNeXI, Tsukuba, Tokyo, November 13-15, 2017, Revised selected papers. (2018) - Unknown
No abstract available